Marination technique influences whole muscle beef jerky salt content and flavor intensity - Skaar, G.R.; Boyle, Elizabeth A. E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Beef jerky is a popular meat snack that is simple to recognize and define. The USDA Food Standards and Labeling Policy Book (FSLPB) allows labeling use of the title “jerky” to a product that has been dried to a moisture-to-protein ratio (MPR) of 0.75:1.0 or less, and states the species or kind (such as beef, pork, or venison) in the name. As long as the product is dried to the required MPR and the species of origin is noted, all additional ingredients used, spice applications, and processing procedures are open for interpretation and application. The USDA FSLPB goes on to state that the product may be cured or uncured, dried, and may be smoked or unsmoked as well as air dried or oven dried. With such a short list of requested, jerky has a great deal of optimization potential for small- and large-scale production. Marination of sliced meat is one stage in the jerkymaking process that is open to variation. Our study compared two common beef jerky marination techniques: 1) traditional marination via extended soaking in a tub, and 2) short-time vacuum tumbling. Additionally, a liquid smoke-based anti-mold spray provided by Kerry Ingredients & Flavors (Monterey, TN) was applied after drying to evaluate the final product for taste differences.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Beef Jerky; Salt; Flavor